Environmental Microbiota of the Neonatology Department at the National Maternal Perinatal Perinatal, Lima, Perú - admin, Investigación Materno Perinatal (2024)
Microbiota ambiental del Departamento de Neonatología en el Instituto Nacional Materno Perinatal, Lima, Perú